Two new aquatic species of Ironus Bastian, 1865 (Nematoda: Ironidae) from Canada - Ebsary, B. A. (Canadian Journal of Zoology, 1985)
Two new species of lronus from freshwater river bottom samples are described and illustrated from Canada. Ironussphincterus n. sp. is recognized by the refractive sphincter between the oviduct and uterus, and the short, elongate conoid tail. Ironus terranovus n. sp. is most similar to I. paramacramphis but differs by shorter body length, narrower head, more anterior vulva, and smaller c value.